Sorting in an urban housing market—is there a~response to demographic change? - Uwe Neumann; Lisa Taruttis (Review of Regional Research, 2021)
Using Dortmund as a~case study we analyse whether rents and housing prices responded to local demographic change in a~German city between 2007 and 2016. In a~two-step analysis based on a~spatial autoregressive hedonic pricing model and a~discrete choice model of housing location we find that during the study period as a~whole, higher local mortality induced a~negative effect on apartment prices and rents. Yet, the neighbourhood effects of local ageing vary across sub-city districts. Most prominently, the study period was characterised by a~strong and rising desire to purchase or rent housing in the vicinity of the city centre. Furthermore, prices for owner-occupied apartments and houses increased rapidly in the more well-off southern part of the city and particularly in a~previously declining community, where a~large-scale urban regeneration and environmental upgrading project has been implemented since 2011. The characteristics of households likely to move to this neighbourhood switched from low to high income.
Keywords: R21; R23; R31; R58; J61; 910; Demographic segregation; Hedonic analysis; Spatial autocorrelation; Discrete choice; Urban policy